The Case for Psychological Computing - Bao, Xuan; Gowda, Mahant; Mahajan, Ratul; Choudhary, Romit Roy (ACM HotMobile, 2013)
This paper envisions a new research direction that we call psychological computing. The key observation is that, even though computing systems are missioned to satisfy human needs, there has been little attempt to bring understandings of human need/psychology into core system design. This paper makes the case that percolating psychological insights deeper into the computing layers is valuable, even essential. Through examples from content caching, vehicular systems, and network scheduling, we argue that psychological awareness can not only offer performance gains to known technological problems, but also spawn new kinds of systems that are difficult to conceive otherwise.